Fiber optic Raman spectroscopy for the evaluation of disease state in Duchenne muscular dystrophy: An assessment using the mdx model and human muscle. Issue 3 (15th July 2022) - Alix, James J. P.; Plesia, Maria; Hool, Sarah A.; Coldicott, Ian; Kendall, Catherine A.; Shaw DBE, Pamela J.; Mead, Richard J.; Day, John C.
Abstract: Introduction/Aims: Raman spectroscopy is an emerging technique for the evaluation of muscle disease. In this study we evaluate the ability of in vivo intramuscular Raman spectroscopy to detect the effects of voluntary running in the mdx model of Duchenne muscular dystrophy (DMD). We also compare mdx data with muscle spectra from human DMD patients. Methods: Thirty 90‐day‐old mdx mice were randomly allocated to an exercised group (48‐hour access to a running wheel) and an unexercised group (n = 15 per group). In vivo Raman spectra were collected from both gastrocnemius muscles and histopathological assessment subsequently performed. Raman data were analyzed using principal component analysis–fed linear discriminant analysis (PCA‐LDA). Exercised and unexercised mdx muscle spectra were compared with human DMD samples using cosine similarity. Results: Exercised mice ran an average of 6.5 km over 48 hours, which induced a significant increase in muscle necrosis ( P  = .03). PCA‐LDA scores were significantly different between the exercised and unexercised groups ( P  < .0001) and correlated significantly with distance run ( P  = .01). Raman spectra from exercised mice more closely resembled human spectra than those from unexercised mice. Discussion: Raman spectroscopy provides a readout of the biochemical alterations in muscle in both the mdx mouse and human DMD muscle.